The Effectiveness of Using Orielly Strategy in Critical Thinking Skills For Students of Primary Sixth class - et. al., Prof. Doctor Abbas Naji Abdulameer, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify the effectiveness of using Orielly strategy in the critical thinking skills for students of primary sixth class. To verify the goal of the research, the null hypothesis was established, that there is no statistically significant difference at a significance level of (0.05) between the average scores of the experimental group students who were taught according to Orielly strategy, and the average scores of the students of the control group who were taught according to the ordinary method, of testing critical thinking skills. The research was limited to sixth primary students, the first semester of the academic year 2020 – 2021 , and to the third, fourth and fifth chapters of the mathematics textbook. Four classes were randomly selected in each of them (15) students to represent the two classes (C, D) of the experimental group, and (A, B) the control group. The total number of the students was (30). The two research groups were rewarded in the variables (previous achievement, previous knowledge test, IQ test, chronological age calculated in months, their parents' academic achievement). (131) behavioral goals were formulated for the three chapters and for the three levels of Bloom's cognitive levels (knowledge, understanding, application). (42) Studies plans were prepared. A test for critical thinking skills (knowledge of assumptions, interpretation, argument evaluation, deduction, conclusion) consisting of (34) paragraphs was prepared. The difficulty coefficient, discriminatory strength, and effectiveness of the wrong alternatives were calculated. The test was applied, and the results of the research indicated that there was a statistically significant difference at a level of significance (0.05), between the average scores of the two groups (experimental and control), in favor of the experimental group in the test of critical thinking skills. This indicates the effectiveness of OReilly strategy in the critical thinking skills of students of sixth class . A number of recommendations were made, including introducing mathematics teachers to modern learning strategies, especially Oreilly strategy for teaching mathematics, and not being limited to traditional methods, to adopt Oreilly strategy in teaching mathematics to the students of sixth class, due to its useful and the effective advantages in critical thinking skills for the students. The research suggested conducting a study to compare the education using Orielly strategy with other teaching methods, other study subjects, different levels of study, and other dependent variables (types of thinking, multiple intelligences ...)